Simultaneous occurrence of multiple aetiologies of polycythaemia: renal cell carcinoma, sleep apnoea syndrome, and relative polycythaemia in a smoker with masked polycythaemia rubra vera. Issue 7 (1st July 2000) - Shih, Lee-Yung; Wang, Ming-Lun; Fu, Jen-Fen
Abstract : A 58 year old male heavy smoker presented with intracranial haemorrhage and erythrocytosis. Four aetiologies of polycythaemia—polycythaemia rubra vera (PRV), renal cell carcinoma, sleep apnoea syndrome, and relative polycythaemia—were found to be associated with the underlying causes of erythrocytosis. He did not fulfill the diagnostic criteria for PRV at initial presentation, but an erythropoietin independent erythroid progenitor assay identified the masked PRV, and the low post-phlebotomy erythropoietin concentration also suggested the likelihood of PRV evolution. This case demonstrates that a search for all the possible causes of erythrocytosis is warranted in patients who already have one aetiology of polycythaemia.